(untitled) (Global Journal of Human-Social Science, 2020)
Summary The objective of this paper is to assess the effect of the quality of institutions in the relationship between bank credit and economic growth in the countries of Sub-Saharan Africa To achieve this econometric estimates were made using the Generalized Moment Method MMG in a dynamic panel of 36 countries in the area over the period from 2000 to 2018 The results obtained show that corruption and political instability have a negative effect on the level of bank credit granted to the private sector The weakness of the legal framework has a negative effect on the level of bank credit granted to the private sector thus limiting economic growth This low level of democracy in these countries therefore has the effect of amplifying this pro-cyclical behavior of gross domestic product per capita The independence of the central bank an effective legal framework political stability and a low level of corruption greatly reduce credit constraints and stimulate lending The quality of institutions has optimal potential for promoting economic growth in Sub-Saharan Africa